Risk Analysis of Operation Igniter Technology System For Rocket Motor X - Nugroho, Widianto; Tjahjadi, Hendrana; Yogaswara, Y. H.; Lestariana, Evie (BRIN Publishing, 2022)
This study discusses risk assessment, and the results of the analysis on the ignition system used on the X rocket. The purpose of this study was to obtain a risk analysis obtained when operating the ignition system on the X rocket. This study used HIRADC (Hazard Identification, Risk Assessment and Determining Control) with a qualitative explanation. The results of the risk assessment in the X rocket motor testing process on the application of the ignition system, there are 10 risks in activities consisting of 8 activities that have a